2002
DOI: 10.1016/s0002-9440(10)64247-2
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Human Immunodeficiency Virus-1 Infection of Human Foreskin and Cervical Tissue Grown in Explant Culture

Abstract: Numerous studies have indicated a protective effect of male circumcision against acquisition of human immunodeficiency virus (HIV)-1. We investigated mechanisms responsible for the possible increased HIV-1 susceptibility of human foreskin. Foreskins from eight pediatric and six adult patients with (n = 3) and without (n = 11) histories of sexually transmitted disease were evaluated. Six cervical biopsies from HIV-1-seronegative women were included as controls. CD4(+) T cells, macrophages, and Langerhans' cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
222
2
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(242 citation statements)
references
References 15 publications
10
222
2
8
Order By: Relevance
“…LCs have been extensively characterized in mucosal tissues involved in HIV-1 infection [8,28], but little is known about the distribution of LCs in the respiratory tract where MV enters the host. We have analyzed the density and phenotype of LCs in the respiratory tract by staining different epithelial tissues for CD1a, Langerin and CD150.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LCs have been extensively characterized in mucosal tissues involved in HIV-1 infection [8,28], but little is known about the distribution of LCs in the respiratory tract where MV enters the host. We have analyzed the density and phenotype of LCs in the respiratory tract by staining different epithelial tissues for CD1a, Langerin and CD150.…”
Section: Resultsmentioning
confidence: 99%
“…Langerhans cells (LCs) are a subset of DCs that are, in humans, characterized by expression of CD1a, the C-type lectin Langerin and the presence of Birbeck granules [6]. LCs reside in the epidermis and stratified epithelial tissues [7][8][9]. Recently, we have shown that LCs form a barrier against HIV-1; LCs capture HIV-1 through Langerin, resulting in internalization of HIV-1 into Birbeck granules and preventing subsequent HIV-1 transmission [10].…”
mentioning
confidence: 99%
“…To test the hypothesis that human foreskin susceptibility to HIV-1 infection is associated with the number of HIV-1 target cells and the expression of HIV-1 co-receptors, Patterson et al 94 quantifi ed CD4+ T cells, macrophages, and Langerhans cells (LCs) in foreskin tissue from pediatric and adult patients without histories of sexually transmitted disease. The authors used cervical biopsies from HIV-1-seronegative women as controls and found that the adult foreskin mucosa contained higher mean proportions of CD4+ T cells (22.4%), macrophages (2.4%), and LCs (11.5%) than both the foreskin mucosa of children (4.9%, 0.3%, and 6.2%) and cervical mucosa (6.2%, 1.4%, and 1.5%).…”
Section: A Decrease In Htlv-1 Viral Shedding and A Reduction In Spreamentioning
confidence: 99%
“…DCs are the first immune cells to encounter HIV-1 in the genital mucosa (7). DCs extend their dendrites into the lumen of mucosal cavities to sense pathogens such as HIV-1 (8).…”
mentioning
confidence: 99%